2000
DOI: 10.1002/1097-0215(20001001)88:1<121::aid-ijc19>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Cycloprodigiosin hydrochloride, H+/CL- symporter, induces apoptosis and differentiation in HL-60 cells

Abstract: Cycloprodigiosin hydrochloride (cPrG • HCl), a novel H+/Cl– symporter, induces acidification of the cytosol and leads to apoptosis in rat and human liver cancer cells. In the present study, the effect of cPrG • HCl on a promyelocytic leukemia cell line (HL‐60) was examined. cPrG • HCl lowered intracellular pH and induced apoptosis through up‐regulation of Fas ligand, activation of stress‐activated protein kinase (SAPK/JNK) and caspase. Apoptosis induced by cPrG • HCl was strongly suppressed when a cell‐permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The red pigment, RP-063, showed similarity to prodigiosin in its physical properties, such as insolubility in water and the absorption spectrum of RP-063 with the maximum absorbance at 533 nm, relatively corresponding with the maximum absorption of prodigiosin and undecylprodigiosin at 540 and 528 nm, respectively (1,9). In addition, in our preliminary experiments, RP-063 was similar to prodigiosin (25) rather than cycloprodigiosin hydrochloride (41) in biological activities such as induction of apoptotic cell death via p38 MAP kinase activation and disorder of intracellular acidic compartment in human monocytic U937 cells (data not shown). Therefore, it was suggested that RP-063 is a red pigment which belongs to the prodigiosin family.…”
Section: Discussionmentioning
confidence: 84%
“…The red pigment, RP-063, showed similarity to prodigiosin in its physical properties, such as insolubility in water and the absorption spectrum of RP-063 with the maximum absorbance at 533 nm, relatively corresponding with the maximum absorption of prodigiosin and undecylprodigiosin at 540 and 528 nm, respectively (1,9). In addition, in our preliminary experiments, RP-063 was similar to prodigiosin (25) rather than cycloprodigiosin hydrochloride (41) in biological activities such as induction of apoptotic cell death via p38 MAP kinase activation and disorder of intracellular acidic compartment in human monocytic U937 cells (data not shown). Therefore, it was suggested that RP-063 is a red pigment which belongs to the prodigiosin family.…”
Section: Discussionmentioning
confidence: 84%
“…2 Prodigiosin also induces apoptosis in cells derived from other human tumors. 3,4 Cycloprodigiosin, another member of the prodigiosin family, induces apoptosis in various cancer cell lines including acute human T-cell leukemia, 17 promyelocytic leukemia, 18 human and rat hepatocellular cancer, 19 human breast cancer, 20 and TNF-stimulated human cervix carcinoma (HeLa). 21 The National Cancer Institute (Bethesda) has also shown that prodigiosin has an average IC 50 of 2.1 mM against a panel of 57 different human cancer cell lines (this information is available on the Internet at www.dtp.nci.nih.gov the NSC number for prodigiosin is 47147-F).…”
Section: Discussionmentioning
confidence: 99%
“…This activity has been implicated in cycloprodigiosin-induced apoptosis because imidazole inhibits both acidification and apoptosis in different human cancer cell lines. [18][19][20] The role of cytoplasmic acidification in the apoptosis of B-CLL cells will be analyzed in the future.…”
Section: Prodigiosin Induces Apoptosis Of B-cll Cellsmentioning
confidence: 99%
“…Also, prodigiosins promoted H+/Cl-, a symport activity leading to acidification of the cytosol. This activity was implicated in cycloprodigiosin-induced apoptosis because imidazole inhibited both acidification and apoptosis in different human cancer cell lines (Yamamoto et al 1999;Yamamoto et al 2000).…”
Section: Drawbacksmentioning
confidence: 99%